Cluster – A New Opportunity and Effectiveness (Texas Journal of Agriculture and Biological Sciences, 2022)
In the article, it is emphasized that a number of achievements have been achieved in the field of Agriculture in recent years through the wide application of clusters in our country, the creation of legal foundations in this regard, of course, opens the way for more opportunities.